(untitled) (Global Journal of Medical Research, 2013)
Polished tapered stems used in hip replacement subside into bone cement without loosening. However, subsidence of rough stems leads to loosening of the prosthesis. There have been no reports on continuous movement of cement and stem. We believed that the relation of stem subsidence to cement differed by stem surface finish. To determine whether this was the case, we compared the pattern of movement of stem and cement in both polished and rough stems in a biomechanical model. Methods Two sizes of polished stems and of roughprocessed stems (rough stems) were fixed into composite femurs with different cement thickness, and a 1-Hz dynamic load was applied for a total of 2 million cycles. An 8-hour no load period was set after every 16 hours of load. Continuous stem motion was measured by a digital displacement gauge, and continuous cement motion was recorded by a strain gauge on an aluminum plate inserted in the cement. All stems subsided downward during the load periods but rose during the no load periods in a 1-day cycle, and a great deal of subsidence were seen by 200,000 cycles– after loading. For polished stems, more than 85% of the total subsidence occurred by 1 million loading cycles, and subsidence rates converged after that. Stem subsidence was not accompanied with cement subsidence. For rough stems, however, subsidence progressed linearly and was accompanied by cement subsidence.The convergence of stem subsidence and lack of synchronization with cement subsidence in polished stems indicated taper slip into cement without loosening. Early subsidence in rough stems leads to progressive subsidence.